Analisando a eficácia de degradação do corante vermelho Congo pelo fungo Pyricularia oryzae - Peres, Laura Rodrigues Munhoz (Universidade Federal de São Carlos, 2024)
Azo dyes, predominantly used in textile industry processes, pose environmental risks and to the health of living beings due to their toxicity and persistence in the environment. Their complex synthetic structure makes them resistant to conventional waste mitigation methods, such as degradation, requiring special treatment in effluents and contaminated soils. This study proposed to analyze the biodegradation and biosorption of the Congo Red dye using the fungus Pyricularia oryzae, which is known as a phytopathogenic in agriculture as it causes blast disease in rice, oat, wheat and triticale crops. Analyzes were carried out using liquid and solid culture media to evaluate the potential for degradation of the dye by the fungus. To isolate the fungus in contact with the dye, PDA culture media was used with the addition of 10, 50 and 100 mg/L of Congo Red. The test tubes with liquid medium were kept in a shaker for 7 days at a temperature of 30°C at a speed of 150 rpm. The solid media were kept in incubation at a temperature of 30°C for 7 days. While visualizing halos indicative of dye degradation proved challenging in solid medium due to the rapid growth and intense pigmentation of the fungus, discernible halos were observed at a concentration of 10 mg/L. In both solid and liquid media, substantial decolorization was achieved at concentrations of 10 and 50 mg/L, with diminished activity observed at 100 mg/L, suggesting a better analysis of adsorption by the Langmuir and Freundlich isotherms, which the biosorption process applies better in the Langmuir model. Finally, the enzymatic activity analysis of the laccase enzyme was carried out with the purpose of verifying the potential of this enzyme. However, there was low dye degradation from the enzymatic activity, meaning that the performance from laccase was unable to oxidize Congo Red in the concentrations higher than 10 mg/L.
Analyzing the degradation efficiency of Congo red dye by the fungus Pyricularia oryzae
Keywords: Biodegradação; Corante sintético; Biorremediação; Degradação; Biodegradation; Synthetic dyes; Bioremediation; Degradation; CIENCIAS BIOLOGICAS::MICROBIOLOGIA